القطاع الخاص ودوره في تنمية الصادرات الصناعية في إطار تحرير تجارة سورية الخارجية - محمود, حبيب; بيطار, شادي; حسن, كنان سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تتناول هذه الدراسة طبيعة الدور الذي يؤديه القطاع الخاص في الاقتصاد السوري من خلال رصد تطور حجم ونوعية هذا الدور ولاسيما في قطاع التجارة الخارجية، وتنبع أهمية ذلك في الاقتصاديات الوطنية كنتيجة لتزايد الاعتماد عليه كمحرك تنموي في البلدان النامية عند تحولها إلى أنموذج اقتصاد السوق، و توجهها للانفتاح على الاقتصاد الدولي وتحرير تجارتها الخارجية، حيث يعول على ديناميكية القطاع الخاص للقيام بدور رئيسي في هذه المرحلة. القطاع الخاص في سورية وفي ظل تبني آليات اقتصاد السوق الاجتماعي و تحرير التجارة الخارجية السورية، فقد أسند له دور متزايد الأهمية في مجالات الإنتاج والتجارة الخارجية مع تراجع لدور القطاع العام، وقد أثبت هذ القطاع ديناميكية وقدرة على الاستجابة للدور المعطى له من خلال زيادة نشاطه في الإنتاج الصناعي وحصته من الصادرات السورية ولاسيما الصادرات الصناعية. This study addresses the nature of the role played by the private sector in the Syrian economy by monitoring the evolution of the size and quality of this role particularly in the foreign trade sector. The importance of that springs as a result of increasing reliance upon it as a development engine in developing countries when the transition to a market economy model with orientation to open up to the international economy and the liberalization of foreign trade, when the reliance is upon the dynamics of the private sector to play a main role in this period. In the light of adopting the model of social economic market and the liberalization of Syrian foreign trade, the private sector has been given an increasing role in production and foreign trade activities. That was combined with the retrieve of public sector. The private sector in Syria had approved its dynamics and ability to meet the given role through increasing its activity in industrial production and its share in export especially in manufactured export.